Using structural context to recommend source code examples - Holmes, Reid; Murphy, Gail C. (Proceedings of the 27th international conference on Software engineering, 2005)
When coding to a framework, developers often become stuck, unsure of which class to subclass, which objects to instantiate and which methods to call. Example code that demonstrates the use of the framework can help developers make progress on their task. In this paper, we describe an approach for locating relevant code in an example repository that is based on heuristically matching the structure of the code under development to the example code. Our tool improves on existing approaches in two ways. First, the structural context needed to query the repository is extracted automatically from the code, freeing the developer from learning a query language or from writing their code in a particular style. Second, the repository can be generated easily from existing applications. We demonstrate the utility of this approach by reporting on a case study involving two subjects completing four programming tasks within the Eclipse integrated development environment framework.